Effect of Adding Curcumin on the Properties of Linseed Oil Organogels Used as Fat Replacers in Pâtés - Gimenez-Castillo, B; Paredes-Toledo, J (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Beeswax‐based organogels were formulated with linseed oil and curcumin according to a statistical design to increase the oxidative stability of spreadable meat products (pâté) where these organogels (OGCur) were incorporated as fat substitutes. The organogels obtained under optimal conditions (9.12% beeswax, 0.54% curcumin) showed a mechanical strength similar to pork backfat determined by back extrusion and high oil binding capacity (OBC; over 90%). The incorporation of curcumin at this concentration did not lead to any change in the arrangement of the crystal network, OBC, and mechanical, thermal, or rheological properties of the organogels. Beeswax organogels with and without curcumin, with a β’ orthorhombic subcell structure, showed a predominant elastic behavior and a melting event wider and shifted to lower temperatures than pure beeswax, suggesting a plasticizer effect of the oil in the wax crystals. The oxidative stability of the organogels under accelerated oxidation conditions increased due to the incorporation of curcumin. A decrease in the curcumin content was found from day 4 at 60 °C, together with a significantly lower formation of both peroxides and malonaldehyde. When pork backfat was partially or totally replaced by OGCur in pâtés, a noticeable protective effect of curcumin against lipid oxidation was found during chilled storage. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: beeswax; linseed oil; curcumin; pate; oxidative stability